Effect of the Natural Herb Amla (Phyllanthus emblica) on Growth, Survival and Disease Resistance in Macrobrachium rosenbergii Juveniles - Mohanan, Salini; Nidhin, B.; Harikrishnan, M.; Prabhakaran, M. P. (Fishery Technology, 2020)
Phyllanthus emblica is a natural herb commonly known as Indian gooseberry or amla, belongs to the family Euphorbiaceae, found natively in India and all parts of this plant are used for several medicinal remedies in Ayurveda. Fruits are highly nutritious and rich source of vitamin C, amino acids and minerals and have tremendous pharmacological applications. In this study three experimental diets composed of ingredients such as fish meal, rice bran, Ground Nut Oil Cake (GNOC), wheat flour, vitamin and mineral mix and different quantities of amla (P. emblica) powder were fed to juveniles of M. rosenbergii (PL 16). Three experimental feed T1,T2 and T3 containing amla powder incorporated at the rate of 0.5 g, 1.0 g and 1.5 g was prepared and feed mixture without amla was used as control. General observation to be given here the juveniles fed with T3 showed maximum growth increment (1.92 ± 0.25 g) than T1 (1.15 ± 0.13 g) and T2 (1.72 ± 0.22 g). The mean growth increment with respect to length showed significant variations (p< 0.005) between treatments. The mean weight of individuals in T2 and T3 groups varied significantly compared to control. FCR values were found in T1 (1.19), comparatively better than T2 (1.59), T3 (1.66) and control (1.91). Whereas SGR values increased from 0.47 to 0.67 from control to T2. The highest percentage survival was recorded in T2 (100 ± 0) during study. In the bacterial challenge test against Aeromonas hydrophila, post larvae fed with T3 (1.5 g 100 g-1) feed showed better survival percentage after 72 h. All the results were statistically checked and significant (p